Neglected but Potent Dry Forest Players: Ecological Role and Ecosystem Service Provision of Biological Soil Crusts in the Human-Modified Caatinga - Szyja, Michelle; Menezes, Artur Gonçalves de Souza; Oliveira, Flávia D. A.; Leal, Inara; Tabarelli, Marcelo; Büdel, Burkhard; Wirth, Rainer (Frontiers in Ecology and Evolution, 2019)
Biological soil crusts (biocrusts) have been recognized as key ecological players in arid and semiarid regions at both local and global scales. They are important biodiversity components, provide critical ecosystem services, and strongly influence soil-plant relationships and successional trajectories via facilitative, competitive, and edaphic engineering effects. Despite these important ecological roles, virtually nothing is known about biocrusts in seasonally dry tropical forests. Here we present a first baseline study on biocrust cover and ecosystem service provision in a human-modified landscape of the Brazilian Caatinga, South America's largest tropical dry forest. More specifically, we explored (1) the impact of disturbance, soil, precipitation, and vegetation-related parameters on biocrust cover in different stages of forest regeneration across a network of 34 0.1 ha permanent plots, and (2) the effect of disturbance on species composition, growth and soil organic carbon sequestration comparing early and late successional communities in two case study sites at opposite ends of the disturbance gradient. Our findings revealed that biocrusts are a conspicuous component of the Caatinga ecosystem with at least 50 different taxa of cyanobacteria, algae, lichens and bryophytes (cyanobacteria and bryophytes dominating) covering nearly 10% of the total land surface and doubling soil organic carbon content relative to bare topsoil. Litter cover, disturbance by goats, and soil compaction were the leading drivers of biocrust cover, while precipitation effects remained undetected and forest regeneration stage influenced the frequency distribution of crust occurrence. Moreover, disturbance reduced biocrust growth by two thirds and carbon sequestration by half. In synthesis, biocrusts are potent carbon sequestering agents of dry forests and may be capable of counterbalancing disturbance-induced soil degradation in those ecosystems globally. As they fix and fertilize depauperated soils, they may play a substantial role in vegetation regeneration in the human-modified Caatinga and may have an extended ecological role due to the ever-increasing human encroachment on natural landscapes. Even though biocrusts benefit from human presence in dry forests, high levels of anthropogenic disturbance could threaten biocrust-provided ecosystem services and call for further, in-depth studies to elucidate the underlying mechanisms